2023
DOI: 10.1038/s41598-023-28224-9
|View full text |Cite
|
Sign up to set email alerts
|

Timely sown maize hybrids improve the post-anthesis dry matter accumulation, nutrient acquisition and crop productivity

Abstract: Delayed sowing of maize hybrids could exacerbate the capability of maximizing the yield potential through poor crop stand, root proliferation, nutrient uptake, and dry matter accumulation coupled with the inadequate partitioning of the assimilates. This study appraised the performance of five recent maize hybrids viz., PMH-1, PJHM-1, AH-4158, AH-4271, and AH-8181 under timely and late sown conditions of the irrigated semi-arid ecologies. Timely sowing had the grain and stover yields advantage of 16–19% and 12–… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Therefore, the remobilization of assimilated from plant leaves and stover to the grain was not complete before the frost and this explains the highest nutrient contents in the plant biomass mass in the last two planting dates compared to the previous planting dates [ 69 ]. These results agreed with Zhiipao et al [ 70 ] who reported the maize leaf and stem phosphorus content was greater in the late sown crop than the timely planting, however, they indicated that maize leaf and stem contents in nitrogen and potassium at maturity were greater in the on-time planting crops than in the delayed planted crops.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the remobilization of assimilated from plant leaves and stover to the grain was not complete before the frost and this explains the highest nutrient contents in the plant biomass mass in the last two planting dates compared to the previous planting dates [ 69 ]. These results agreed with Zhiipao et al [ 70 ] who reported the maize leaf and stem phosphorus content was greater in the late sown crop than the timely planting, however, they indicated that maize leaf and stem contents in nitrogen and potassium at maturity were greater in the on-time planting crops than in the delayed planted crops.…”
Section: Discussionsupporting
confidence: 91%
“…Despite the two cultivars being among the top cross hybrids in the East Africa region, the model calibration results indicated that H614 require more heat units to attain anthesis and reach physiological maturity. Longer growth duration in long‐maturing varieties compounded by optimal weather conditions at critical crop phases increases dry matter accumulation and allocation to kernels, thus improving crop productivity (G. Liu et al., 2023; Zhiipao et al., 2023). The varied response of SDs and cultivars on maize yield aligns with other studies conducted in the African agricultural systems (Adnan et al., 2017; Tesfaye et al., 2017; Tofa et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The samples were air-dried in a perforated brown paper bag and then oven-dried at 65 ± 2°C to a constant weight. The ovendried samples of each plant part were weighed separately, and the obtained values were used for the determination of dry matter accumulation (DMA), remobilization (DMR), remobilization efficiency (DMRE) and contribution to the grain yield (DMRG) using Equation 1 (Ntanos & Koutroubas, 2002;Zhiipao et al, 2023). The nutrients' (N, P and K) concentration in different plant parts were analysed by employing modified kjeldahl digestion process for total-N, Vanadomolybdo-phosphoric acid method for total-P and flame photometer for total-K (Prasad et al, 2006).…”
Section: Plant Observations Sampling and Measurementsmentioning
confidence: 99%
“…The performance of genotypes grown under different environments can be evaluated using various stress indices viz., geometric mean productivity (GMP), stress susceptibility index (SSI), tolerance index (TOL), yield stability index (YSI) and stress tolerance index (STI), which have often been used in screening the genotypes (Jamshidi & Javanmard, 2018; Tyagi et al., 2020). In addition, the rooting pattern of crop could further benefit the performance and its capability to adapt under stress and non‐stress environments, as root systems have direct impact on shoot growth particularly in the formation of grain (Zhiipao et al., 2023). Further, crop genotypes with greater root length density (RLD) and total root length have been reported to improve the acquisition of nutrients and water, thereby enhanced the shoot biomass and photosynthetic activity resulting in more yield stability (Tran et al., 2015) under the varied environments.…”
Section: Introductionmentioning
confidence: 99%